The Urgency of Establishing LPPDP as an Effort to Strengthen Personal Data Protection: A Comparison between Indonesia, Hong Kong and Singapore - Yunanda, Veris; Wiranata, I Gede AB; Agustin, Yennie; Rohaini, Rohaini; Zazili, Ahmad (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2024)
PurposeThe aim of this research is to analyze the urgency of establishing the LPPDP in strengthening personal data protection laws in Indonesia through a comparison of laws and practices in Hong Kong and Singapore and to determine the opportunities and challenges of establishing the LPPDP in Indonesia. MethodologyThe research uses normative legal research methods with a statutory approach, a conceptual approach and a comparative approach. ResultThe results show that the existence of an independent LPPDP will strengthen the personal data protection law effectively and comply the adequate level of protection with other developed countries. Thus, the President must immediately establish LPPDP regarding the minimum requirements for the DPA's establishment in international practice. ContributionLaw Number 27 of 2022 concerning Personal Data Protection (UU PDP) has directly mandated the establishment of a data protection authority which determined by the President. The LPPDP has projected to become an authority that acts as a supervisor and law enforcer for personal data protection in Indonesia, the LPPDP must be able to perform its functions, duties, and authorities independently. LimitationHowever, instead of achieving this noble goal, there are several recommendations that can be applied in establishing the formation of LPPDP, whether in the form single supervisory authority or ministry based-models.